Challenges in developing fish‐based ecological assessment methods for large floodplain rivers - J. J. DE LEEUW; A. D. BUIJSE; G. HAIDVOGL; M. LAPINSKA; R. NOBLE; R. REPECKA; T. VIRBICKAS; W. WIŚNIEWOLSKI; C. WOLTER (Fisheries Management and Ecology, 2007)
Large European floodplain rivers have a great diversity in habitats and fish fauna, but tend to be heavily modified. The complexity of these river systems and their multiple human impacts pose considerable challenges for assessment of their ecological status. This paper discusses: (1) the application of historical information on fish fauna and habitat availability to describe reference conditions; (2) responses of fish assemblages to human disturbance by comparing various rivers and river segments with different impacts and/or time series within rivers; (3) the role of floodplain water bodies in ecological assessment; and (4) monitoring of large rivers using different gears and sampling designs for main channels and floodplain habitats. The challenge for the future is to standardise and calibrate sampling methods and data to enhance the potential for ecological assessment of large rivers.